2012
DOI: 10.1093/geront/gns086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Psychological Intervention in a Primary Health Care Center for Caregivers of Dependent Relatives: A Randomized Trial

Abstract: Psychological group intervention in the context of PHC, aimed at the CGs of dependent persons with dementia and other disabilities, has improved mental health condition in CGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 37 publications
1
37
0
3
Order By: Relevance
“…The second group of authors who added training in selfhelp techniques to the cognitive behavioral treatment also found a positive impact on the primary outcomes: dysfunctional thoughts and mental health of caregivers of the intervention group. The secondary outcomes quality of life and burden did not differ after receiving treatment [97]. Finally, Passoni et al concluded that both intervention groups had less need for care or assistance compared to control group participants, but anxiety and depressive symptoms did not differ [98].…”
Section: Cognitive Behavioral Therapy Interventionsmentioning
confidence: 98%
“…The second group of authors who added training in selfhelp techniques to the cognitive behavioral treatment also found a positive impact on the primary outcomes: dysfunctional thoughts and mental health of caregivers of the intervention group. The secondary outcomes quality of life and burden did not differ after receiving treatment [97]. Finally, Passoni et al concluded that both intervention groups had less need for care or assistance compared to control group participants, but anxiety and depressive symptoms did not differ [98].…”
Section: Cognitive Behavioral Therapy Interventionsmentioning
confidence: 98%
“…These programmes include group education (Marriott et al 2000, Gallagher-Thompson et al 2001, Hepburn et al 2001, M arquez-Gonz alez et al 2007, home visits with/or telephone consultation and support (Belle et al 2006, Gallagher-Thompson et al 2007, Moniz-Cook et al 2008, Bormann et al 2009, Elliott et al 2010) and support groups (Fung & Chien 2002, Chien & Lee 2008, Gavrilova et al 2009, Elliott et al 2010. FCGs' depressive symptoms were also significantly improved by randomized control trials of a pleasant-events programme (Moore et al 2013), an individual teaching programme based on coping strategy , an 8day daily telephone-monitoring stress and mood programme (Zarit et al 2014), problem-solving therapy (Garand et al 2014) and psychological/education interventions (Joling et al 2012, Rodriguez-Sanchez et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al, 2012;Werner et al, 2012;Hayashi et al, 2013) or as an outcome measure in intervention studies (e.g. Cheng et al, in press; Correspondence should be addressed to: Sheung- Tak Gaugler et al, 2013;Rodriguez-Sanchez et al, 2013). While it is most often used as a global measure, researchers have attempted to discover distinguishable dimensions within the scale in order to provide more differentiated information about the impact of caregiving.…”
Section: Introductionmentioning
confidence: 99%